No evidence for spread of Plasmodium falciparum artemisinin resistance to Savannakhet Province, Southern Laos - Mayfong Mayxay (2018)
We conducted an open-label, randomized clinical trial to assess parasite clearance times (PCT) and the efficacy of 4 mg/kg (group 1, n = 22) and 2 mg/kg (group 2, n = 22) of oral artesunate for three days followed by artemetherlumefantrine in patients with uncomplicated Plasmodium falciparum malaria at Xepon Interdistrict Hospital, Savannakhet Province in southern Laos. Slides were read in duplicate. The overall mean (95% confidence interval; range) PCT in hours was 23.2 (21.2-25.3; 12-46) and 22.4 (20.3-24.5; 12-46) for the first and second microscopists, respectively (P = 0.57). Ten (23%) patients remained parasitemic on day 1 after treatment (4 [18%] in group 1 and 6 [27%] in group 2; P = 0.47). No patient had patent asexual parasitemia on the second and third days of treatment. The 42-day polymerase chain reaction-corrected cure rates were 100% in both treatment groups. Serious adverse events did not develop during or after treatment in any patients. In conclusion, no evidence of P. falciparum in vivo resistance to artesunate was found in southern Laos. Copyright © 2012 by The American Society of Tropical Medicine and Hygiene.